A rational pension reform package: Hungary, 2025 - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
As part of the Recovery and Resilience Plan (RRP, 2023), the Hungarian government pledged to reform the pension system. The main themes are sustainability and adequacy. The pension plan is to be discussed publicly and put into law by March 2025. The last detailed official pension study was the 2016-discussion paper of the Hungarian National Bank which should be updated. The present study is a private work which may contribute to the improvement of the current pension system. The current and the projected states of the Hungarian pension system are outlined, and then simple and complex reforms are formulated. Naming just two reform steps, I start with the simplest step: the return to public discussion steered by a revitalized Fiscal Council and end with the most complex: the introduction of the flexible (variable) retirement age.
Keywords: H55; 330; pension systems; pension policies; pension reforms; Hungary